Micro combined heat and power technologies and control for residential applications. (16th March 2010) - Shaneb, Omar A.; Coates, Graham; Taylor, Phil C.
Residential applications are considered among the most important areas for substantial reduction of CO2 emissions because they represent a major part of the total consumed energy in those countries. In order to achieve a significant CO2 reduction, many initiatives must be adopted in the policy of these countries. One of these initiatives is to introduce micro combined heat and power (μCHP) systems into residential energy systems, since they offer several advantages such as the ability to burn not just natural gas but renewable fuels (Taylor, 2005). This paper summarises key points that outline the trend of previous research carried out in the field of μCHP systems in residential energy systems, especially for single dwellings. The reviewed areas include: residential energy demand and μCHP, technologies and auxiliary components used in residential μCHP systems, and control strategies and techniques for these systems.